EFFECT OF GENDER AND AGE ON THYROID FUNCTION TESTS (TFT) AT HAYATABAD MEDICAL COMPLEX PESHAWAR, PAKISTAN (The Research of Medical Science Review, 2024)
Background: Thyroid function tests (TFTS) are essential for evaluating thyroid function, sense they provide information about thyroid gland. Function based on factors including TSH. T3, T4. These characteristic can be effected by a number of factors, such as age and gender, which may have in effect on the diagnosis and treatment of thyroid problems. Objective: The objective of current study were to check the fffect of age on Thyroid hormone level. To find out gender-based variation on thyroid function test (TFT) and to determine relationship between age, Gender and thyroid function Methodology: We conducted a cross-sectional secondary data analysis on participants who visited OPD of Hayatabad Medical Complex. A total 139 participants were included in our study. Results: Correlation study revealed that age is directly related to the thyroid hormone level. With increasing age thyroid hormone level also increase specifically T4 .Gender variation For T3 and T4 also showed positive result with T4 Being observed in Higher Number in Male relative to Female. Regression analysis Produced negative Result for the effect of age on thyroid hormone level while or gender base variation the result were statistically significant P value being 0.048 for the effect of male Gender on T4 hormone. CONCLUSION: The thyroid gland produces hormones T3 and T4, controlling metabolic rate and vital functions. Deranged levels can cause thyroid-related problems in both men and women. Research shows age correlates with T3, but gender may affect T4 level.